2015
DOI: 10.3109/21681805.2015.1004643
|View full text |Cite
|
Sign up to set email alerts
|

Role of 3T multiparametric magnetic resonance imaging without endorectal coil in the detection of local recurrent prostate cancer after radical prostatectomy: the radiation oncology point of view

Abstract: This is the first study to find a significant relationship between the PSADT and the rLR through MRI. Patients with PSADT longer than 14 months or pre-SRT PSA above 0.5 ng/ml benefited most from 3TmMRI. Its routine use could have significant clinical implications for SRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Several factors, including PSA levels at recurrence, the PSADT, and the presence of compromised resection margins, have all been significantly associated with mpMRI findings. Several authors have defined pre-radiotherapy PSA cut-off values, ranging from > 0.3[ 37 ] to > 0.5[ 40 ] or ≥ 0.54[ 39 ] ng/mL, as clinical predictors of MRI positivity. Eifler et al[ 19 ] reported a higher probability of visible local relapse in patients with PSADT > 14 mo.…”
Section: Detection Of Relapse After Radical Prostatectomymentioning
confidence: 99%
“…Several factors, including PSA levels at recurrence, the PSADT, and the presence of compromised resection margins, have all been significantly associated with mpMRI findings. Several authors have defined pre-radiotherapy PSA cut-off values, ranging from > 0.3[ 37 ] to > 0.5[ 40 ] or ≥ 0.54[ 39 ] ng/mL, as clinical predictors of MRI positivity. Eifler et al[ 19 ] reported a higher probability of visible local relapse in patients with PSADT > 14 mo.…”
Section: Detection Of Relapse After Radical Prostatectomymentioning
confidence: 99%
“…Thus, after RP, the optimal PSA cut-off level for choline PET/CT analysis seems to be between 1 and 2 ng/mL [23], while for MRI, the corresponding value appears to range from 0.3 to 0.54 ng/mL [5]. In addition to the PSA value, several studies have reported that PSA kinetics (PSADT, PSA velocity) are strong predictors for positive PET and MRI findings, even in patients with low PSA values [4, 5, 23]. We found that PSADT was significantly associated with the type of pelvic recurrence: patients with a higher PSADT had an increased probability of local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we did not use endorectal coil and this may have influenced the reliability of the MRI images [26]. Nevertheless, in patients with tumor recurrence after RP, the tumor detection rate using a 3T MRI seems not to be influenced by the type of coil [4]. Lastly, in our study 4 patients received ADT before MRI and PET/CT, which could have a limited uptake on the choline PET/CT and caused morphological changes and alterations in the parameters of the DWI and DCE on the MRI [27, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 55 This has been further supported by a recent trial using 3 T MRI without EC, which showed that the probability of radiographic local recurrence was significantly higher in patients with PSA >0.5 ng/mL. 56 However, these are retrospective studies, and no histopathological confirmation was undertaken to confirm the interpretation of the mp-MRI findings. Additionally, to our knowledge, there are no comparative studies evaluating the value of increasing the field strength of the magnet and using an EC in detecting local recurrence.…”
Section: Use Of Multi-parametric Mri In Ctv Delineationmentioning
confidence: 96%